Multiwavelength Variability Analysis of 3C 279 - Patiño-Álvarez, Víctor M.; Fernandes, Sunil; Chavushyan, Vahram; López-Rodríguez, Erique; León-Tavares, Jonathan; Schlegel, Eric M.; Carrasco, Luis; Valdés, José R.; Carramiñana, Alberto (Frontiers in Astronomy and Space Sciences, 2017)
We present a multifrequency analysis of the variability in the flat-spectrum radio quasar 3C 279 from 2008 to 2014. Our multiwavelength datasets range from 1mm to gamma-rays, with additional optical polarimetry. Cross-correlation analysis shows a significant correlation between the UV continuum emission, the optical and NIR bands, at a delay consistent with zero, implying co-spatial emission regions. We also find a correlation between the UV continuum and the 1 mm data, which implies that the dominant process in producing the UV continuum is synchrotron emission. Based on the behaviour of the gamma-ray light curve with respect to other bands, we identified three different activity periods. During period A we find a significant correlation at zero delay between the UV continuum and the gamma-rays, implying co-spatial emission regions which points towards synchrotron self-Compton as dominant gamma-ray emission mechanism. During period C we find a delay between the UV continuum and the gamma-rays, as well as a correlation at zero delay between X-rays and gamma-rays, both results implying that external inverse Compton is the dominant gamma-ray emission mechanism. This is the first time that observational evidence is presented for a change in the dominant gamma-ray emission mechanism in a blazar. During period B there are multiple flares in the bands from 1mm to UV, however, none of these show a counterpart in the gamma-rays band. We propose that this is caused by an increase in the gamma-ray opacity due to electron-positron pair production.